The motor deficits caused by Parkinson's disease are not able to block adjustments for a safe strategy during obstacle crossing in individuals with moderate disease - Pereira, Vinícius Alota Ignácio [UNESP]; Barbieri, Fabio Augusto [UNESP]; Vitório, Rodrigo [UNESP]; Simieli, Lucas [UNESP]; Lirani-Silva, Ellen [UNESP]; Orcioli-Silva, Diego [UNESP]; Gobbi, Lilian Teresa Bucken [UNESP] (FapUNIFESP (SciELO), 2015)
The aim of this study was to verify whether patients with Parkinson's disease (PD) are able to adjust their motor behavior according to restrictions imposed by the task instruction during walking with obstacle crossing. Eighteen elderly people (moderate motor compromise) with a diagnosis of PD walked on a pathway and cross an obstacle according to the following conditions: walking at preferred velocity; walking at maximum vertical elevation of the feet to cross the obstacle; walking at maximum step length to cross the obstacle; walking at maximum velocity. The modulations were directly related to the instructions provided to patients with PD before performing each task, which seems to indicate that attentional cues can influence and benefit strategies during obstacle crossing. In conclusion, patients with PD are able to adjust walking during obstacle crossing according to instructions given to them, which increases their safety.
Keywords: Gait; Movement; Parkinson's disease; Spatial behavior; Time and motion studies